VDC_100102370126.0X000001. Issue 3 (March 2018) - Maeda, Takashi; Kayashima, Hiroto; Imai, Daisuke; Takeishi, Kazuki; Harada, Noboru; Tsujita, Eiji; Tsutsui, Shinichi; Matsuda, Hiroyuki
Postoperative pancreatic fistula (PF) is a relatively frequent and occasionally fatal complication of pancreatoduodenectomy (PD). Several risk factors for PF have been reported, including high drain amylase level (D-AMY). Among the 140 consecutive patients who underwent PD, we analyzed 110 cases with D-AMY measurements over time after PD. According to the D-AMY change, we divided patients into five patterns and defined delayed PF cases. We analyzed clinical characteristics, including serum amylase and D-AMY, and examined the correlation between the period of drain insertion and PF grade. In 15 delayed PF cases, 12 cases were grade B or C, pancreatic cancer was less frequent, pancreatic ducts were smaller, and soft pancreas texture was more commonly observed. The D-AMYon postoperative day (POD) 1 was higher in cases of delayed PF compared with non-PF cases ( P < 0.0001). In 28 cases with drain removal before POD 7, grade B or C PF was not observed afterward. The average D-AMYon POD 1 in cases with drain removal before POD 1 was significantly lower than in delayed PF cases. Although further studies are required to determine the most appropriate timing of drain removal, it is thought that intra-abdominal drains should be removed within seven days of PD in cases without signs of PF. On the other hand, delayed PF should be considered in cases of soft pancreas texture and/or high D-AMY on POD 1, even if D-AMY levels are low on POD 3 or decreasing on POD 5.